2004
DOI: 10.1109/joe.2004.841424
|View full text |Cite
|
Sign up to set email alerts
|

Solitons Northeast of Tung-Sha Island During the ASIAEX Pilot Studies

Abstract: In a recent study, satellite images have shown that internal solitons are active in the northern South China Sea (SCS). During the Asian Seas International Acoustic Experiment (ASIAEX) pilot studies, current profiler and thermistor chain moorings were deployed in the spring of 1999 and 2000 to investigate internal solitons northeast of Tung-Sha Island on the continental slope of the northern SCS. Most of the observed internal solitons were first baroclinic mode depression waves. The largest horizontal current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(90 citation statements)
references
References 38 publications
(66 reference statements)
5
84
0
1
Order By: Relevance
“…In a pilot program Yang et al (2004) observed a single mode-two wave in 426 m deep water. Yang et al (2009Yang et al ( , 2010 analysed mooring data obtained during the VANS/WISE program which was conducted in 2005 and 2006 in the vicinity of the ASIAEX field program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a pilot program Yang et al (2004) observed a single mode-two wave in 426 m deep water. Yang et al (2009Yang et al ( , 2010 analysed mooring data obtained during the VANS/WISE program which was conducted in 2005 and 2006 in the vicinity of the ASIAEX field program.…”
Section: Discussionmentioning
confidence: 99%
“…Mode-two solitary-like waves were observed during the ASIAEX experiment (Orr and Mignerey, 2003) but not reported on in detail. Observations of a mode-two ISW made during a pilot study for the ASIAEX experiment were reported by Yang et al (2004). Many mode-two solitary-like waves were observed at 350 m depth in a nearby region during the joint VANS/WISE experiments (Yang et al, 2009.…”
Section: K G Lamb and A Warn-varnas: Shoaling Internal Solitary Wavesmentioning
confidence: 95%
“…During April 2000, there was a much larger Kuroshio intrusion than during April 2001 [3]. The solitons observed at IW1 during 2000 were also larger than the solitons observed nearby at S7 during 2001 [49]. So, there is some incidental evidence to support the idea that more energetic Kuroshio intrusions that loop around the Luzon Ridge favor the generation of larger amplitude internal waves.…”
Section: B Wave Amplitudes In Cluster 1 Versus Clustermentioning
confidence: 91%
“…The terrain of the strait makes it an active ground for the generation of internal waves. Recently, dramatic internal tides, solitary waves and bores were observed at locations from LS to the northern South China Shelf (NSCS) both in satellite images and field observations Hsu & Liu, 2000;Liu et al, 2006Liu et al, , 2008Yang et al, 2004;Zhao, Klemas, Zheng, & Yan, 2004).…”
Section: Introductionmentioning
confidence: 99%